2009
DOI: 10.1097/meg.0b013e328310abd1
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide for recurrent intestinal variceal bleeding in patients without portal hypertension

Abstract: We report on the efficacy of octreotide acetate in two patients with intestinal phlebectasia and no evidence of portal hypertension or mesenteric thrombosis. Patient 1 was a 46-year-old woman with primary pulmonary arterial hypertension. She required repeated transfusions for recurrent episodes of gastrointestinal bleeding (GIB). Intraoperative enteroscopy revealed wide-spread small bowel phlebectasia and intestinal resection was not performed. Blue rubber-bleb syndrome, portal hypertension and mesenteric thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…9 Medical management of EVs is lacking; however, somatostatin analogue therapy has proved to have merit in preventing intestinal variceal bleeding. 10 This is a case of DV secondary to scar tissue that was still amenable to treatment with beta-blockade and octreotide. On further assessment, no pre-hepatic, posthepatic, or intrahepatic cause was identifiable that would constitute a diagnosis of noncirrhotic PH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Medical management of EVs is lacking; however, somatostatin analogue therapy has proved to have merit in preventing intestinal variceal bleeding. 10 This is a case of DV secondary to scar tissue that was still amenable to treatment with beta-blockade and octreotide. On further assessment, no pre-hepatic, posthepatic, or intrahepatic cause was identifiable that would constitute a diagnosis of noncirrhotic PH.…”
Section: Discussionmentioning
confidence: 99%
“…High postsurgical mortality rates have resulted in surgical procedures being superseded by endoscopic and radiological alternatives, which have demonstrated modest success 9 . Medical management of EVs is lacking; however, somatostatin analogue therapy has proved to have merit in preventing intestinal variceal bleeding 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case report, two patients who were diagnosed with intestinal variceal bleeding received octreotide over a span of 74 mo and 27 mo, respectively. The treatment was effective in preventing recurrent episodes of GI bleeding[ 73 ]. Another study reported a case of an 81-year-old female who presented with hematochezia and was diagnosed with small bowel varices that were caused by compression of the superior mesenteric vein due to a large pancreatic neuroendocrine tumor[ 74 ].…”
Section: Ectopic Intestinal Varicesmentioning
confidence: 99%